Guldringen fra Emmerlev og dens ophav - Hartvig, Anders; Pommergaard, Kirstine (Arkæologi i Slesvig-Archäologie in Schleswig, 2026)
Since 2016, metal detectorists have searched the area between the modern-day village of Emmerlev and the local church, and in 2020 a unique object was found – a gold finger ring with a garnet. This ring is the first of its kind known in Denmark, and studies of this ring have revealed a connection to one of the main elite powers of Europe in late 5th to the late 8th centuries AD: the Merovingians. The way the ring is constructed – trefoil shaped filigree on the side of the ring plate and the way the ring band is mounted on the back of the ring plate with spiral ends are a known ring type produced by craftsmen in the Merovingian area of central Europe. Parallels have shown that the rings are most likely connected directly to the Merovingian lineage; a signet ring with the same construction as the one found in Emmerlev bears the inscription »ARNEGVNDE REGINE«. Arnegunde was the name of the fourth wife of Chlotar II (584 –629 AD), Merovingian king of the Franks. Emmerlev is located in a landscape where the presence of powerful individuals for many centuries is clearly indicated by the large number of metal finds, by the sheltered location near the Wadden Sea, and by the combination of finds known from Emmerlev. Considering the pit houses with Frisian turned ceramics and the presence of sceattas and Frisian brooches, it is a possible interpretation that Emmerlev was a trading post, which one could have entered from the Wadden Sea. This area must have been controlled by an elite family with close connection to the socio-economic system of Central Europe, and the elite power of the Merowingians and Frisians.